PECULIARITIES OF SPREADING OF SPRUCE STANDS DRYING IN GORGANY - Rak, A. Yu.; Olijnyk, V. S. (Forestry and Forest Melioration, 2018)
Introduction In the Carpathian region, very important problem of modern forestry is the drying of the main forest creating culture – Рісеа abies (L.) H. Karst., which has begun in the 1990s and continues nowadays. Despite the relatively wide coverage of spruce sustainability issues, a number of issues remain unclarified. It concerns mostly the quantities of foci of overall and partial drying of the spruce and mixed plantings and their dependence on relief and weather conditions. These issues are especially topical for the Gorgany, the central mountainous massif of the Ukrainian Carpathians, with their pervasive spread of spruce and the most complex relief-weather and ecological and vegetation conditions in the region. Spruce stands drying here may be increased considerably by harmful natural phenomena thereby threatening ecological and silvicultural and forestry situation. Materials and Methods The study of the spruce stands drying was conducted in forest conditions, which are typical for Gorgany, in State Enterprise “Vyhodske Forest Economy”. Quantifying this phenomenon is based on materials of drying areas allotment into overall and partial felling, with the participation of one of the co-authors of this article. In the data analysis, the natural and forestry peculiarities of the areas (exposition, height and steepness of slopes, forest type, composition, age and density of stands) were taken from the forest taxation descriptions. Under the field conditions, the area and the stock of damaged wood on it have been determined by the common methods. The analysis involved 107 areas of drying in 2014–2015, 84 of them are overall and 21 – partial. For this purpose, the data on areas of drying in Svichivske forestry in 2009–2015 has been compared with rainfall rates obtained from a nearby weather station “Dolyna”. In addition, the part of dead wood spruce has been determined in this forestry on five sample plots depending on composition and completeness of the stands. Results Distribution of drying spruce plantations depends on a number of forestry and abiotic factors. This phenomenon is most characteristic for the slopes up to 1,200 m above sea level height. In this case, the partial drying dominates at the altitude less than 800 m and the overall, at 800–1,200 m. On the slopes of the southern exposure, the overall drying area is 1.8 times larger than that on the northern ones. This process is intensified as the slopes steepness increases. The areas of partial drying depend slightly on exposure and steepness of slopes. Stability of spruce plantations depends significantly on the July rainfalls. Under near-normal and bigger precipitations the following amounts of spruce drying are minor, and by their lowering, they rise sharply. This phenomenon is most common in pure spruce. If the share of this species is 5–6 units in the stand, drying is mild. The overall drying mainly occurs in understocked and medium stocked stands with the age of more than 50 years; the partial one occurs in 50–70 years old medium and fully stocked plantations. Conclusions To minimize the spread of spruce drying it is appropriate to comply certain classic forestry requirements: implementation of forest growing only on forest typology basis, maintaining medium and, especially, full stoking of the stands and clear differentiation of the forestry operation depending on the characteristics of mountain terrain. On the steep slopes of the southern exposure, the management mode should be more limited than on other categories of relief.